2012
DOI: 10.1039/c2cc17274g
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical and biological investigation of novel luminescent Ru(ii)-polypyridyl-1,8-naphthalimide Tröger's bases as cellular imaging agents

Abstract: The synthesis and photophysical properties of 1 and 2, two Ru(II)-polypyridyl based-1,8-naphthalimide Tro¨ger's bases, are described; these were found to stabilize double stranded DNA, undergo rapid cellular uptake, displaying good luminescence without affecting cell viability even after 24 hours of incubation.Tro¨ger's base was first discovered in 1887, formed upon reaction of para-toluidine with formaldehyde under acidic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 45 publications
0
53
1
1
Order By: Relevance
“…Confocal microscopy was carried out in order to provide visual evidence of the localisation of Ru·Nap and Ru·2Nap in HeLa cervical cancer cells. Populations of live cells (0.5 × 10 5 ) were incubated with both complexes (30 µM) at 37°C for 4 and 24 h before being treated with the fluorescent nuclear stain DAPI and viewed using an Olympus FV1000 Although we do not demonstrate colocalisation with any specific organelles for this study, our previous work in this area 32,54 has demonstrated that related Ru(II) complexes localise predominantly within the mitochondria, leading to perinuclear clustering, with some localisation observed in the lysosomes and the endoplasmic reticulum. Similar localisation results has been seen by several other researchers.…”
Section: Cellular Uptake Localisation and Viability Studiesmentioning
confidence: 76%
See 1 more Smart Citation
“…Confocal microscopy was carried out in order to provide visual evidence of the localisation of Ru·Nap and Ru·2Nap in HeLa cervical cancer cells. Populations of live cells (0.5 × 10 5 ) were incubated with both complexes (30 µM) at 37°C for 4 and 24 h before being treated with the fluorescent nuclear stain DAPI and viewed using an Olympus FV1000 Although we do not demonstrate colocalisation with any specific organelles for this study, our previous work in this area 32,54 has demonstrated that related Ru(II) complexes localise predominantly within the mitochondria, leading to perinuclear clustering, with some localisation observed in the lysosomes and the endoplasmic reticulum. Similar localisation results has been seen by several other researchers.…”
Section: Cellular Uptake Localisation and Viability Studiesmentioning
confidence: 76%
“…[22][23][24][25][26][27][28][29] We have also developed several examples of DNA targeting binders, based on the use of 1,8-naphthalimide derivatives. [30][31][32][33][34][35][36][37][38] Such structures have tuneable electronic properties, and have been shown to exhibit good DNA binding affinity through either intercalation or groove binding. [39][40][41][42][43][44] In addition to being effective DNA intercalators or groove binders, the 1,8-naphthalimides can also act as sensitising antenna for the Ru(II)-based metal-to-ligand charge transfer (MLCT) emission, allowing for the population of the excited state using two excitation channels.…”
Section: Introductionmentioning
confidence: 99%
“…To this end we have actively been involved in the use of naphthalimide based ligands to prepare novel transition metal complexes, for sensing, as probes for DNA binding, as cellular imaging agents, as well as developing them further to give naphthalimide containing Tröger's base derivatives. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] With the view of exploring the possibility of incorporating such ligands into larger coordinating networks, metallo organic frameworks or supramolecular complexes, we embarked on the development of novel structurally simple naphthalimide ligands. Herein we report the synthesis of monodentate pyridyl containing 4-substituted naphthalimide based ligands L 1 and L 2 and the resulting complexation studies with Cu(II) metal salts [Cu(OAc) 2 , Cu(ClO 4 ) 2 ·6H 2 O and Cu(CF 3 SO 3 ) 2 ] in order to assess their applicability as synthons in developing higher order supramolecular architectures.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, various of TB derivatives were synthesized and applied in the eld of molecular recognition [2], chiral ligands [3][4][5], DNA probes [6,7], stereo selective catalysis [8][9][10][11][12], drug development [13,14], CO 2 capture [15,16], bioorganic chemistry [17][18][19], electroluminescent materials [20,21] and supra molecular chemistry [22] in the last two decades. Their wide range of applications is based on their huge rigidity, V-shaped twisted con guration, N-central chirality and C 2 -symmetry.…”
Section: Discussionmentioning
confidence: 99%